Solvent-free selective oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over U3O8-supported nano-gold catalysts - Choudhary, Vasant R.; Dumbre, Deepa K. (Applied Catalysis A-General, 2010)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide over different uranium oxide supported nano-gold catalysts in the absence of a solvent has been thoroughly investigated. The influences of catalyst parameters [viz, method of gold deposition (impregnation, co-precipitation, deposition-precipitation and homogeneous deposition-precipitation), gold loading (08 wt%) and catalyst calcination temperature (100-900 degrees C)] on the catalyst performance have been investigated. The influence of reaction conditions [viz, reaction time (0-2 h) and temperature (25-94 degrees C)] on the process performance has also been studied. The Au/U3O8 catalyst prepared by the homogeneous deposition-precipitation and calcined at 400 degrees C showed very high activity (100% benzyl alcohol conversion with >85% selectivity for benzaldehyde) in the process for a short reaction period (0.5 h) at 94 degrees C. The catalyst also showed excellent reusability in the process. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Au/U3O8 catalyst; Benzaldehyde; Benzyl alcohol; Nano-gold; Partial oxidation; tert-Butyl hydroperoxide